Experimental investigation of tyre–road friction considering topographical roughness variation and flash temperature. (March 2023) - Grigoriadis, Kyriakos; Mavros, Georgios; Knowles, James; Pezouvanis, Antonios
Abstract: Predicting tyre–road friction requires various inputs that are known with differing levels of confidence. This paper studies the prediction and associated experimental confirmation of rubber friction on real roads at high sliding speeds. Friction predictions are obtained from Persson's flash temperature model: the topography of the road surface is measured using an optical profilometer, while the rubber's viscoelastic modulus is obtained through Dynamic Mechanical Analysis. A newly developed friction tester performs in-situ friction measurements, while controlling and monitoring bulk and contact surface temperature, respectively. Local topographical road roughness variations were identified as a major contributing factor leading to predicted friction variations of over 50%, while the flash temperature predictions showed good correlation with temperature measurements from near the rubber–road interface. Highlights: Rubber friction testing with flash temperature measurement under real conditions. Persson's flash temperature model without adhesion showed agreement with experiment. Rubber background temperature is less important in practical situations. Partial validation of flash temperature predictions.